Rio de Janeiro : The monocle travel guide series. - Monocle, ....- (Berlin : Gestalten, 2016)
With its glorious coastline, dramatic mountains and urban rainforest, Rio de Janeiro is a city that hits you between the eyes with its natural beauty. But there’s plenty to discover here that isn’t instantly self-evident. From lively neighbourhood bars and an intricate beach culture to sculptural gardens and concrete modernist buildings, there is a lot more to Rio than bronzed bodies on Ipanema Beach.
Keywords: reisgids